The Responsibility of Social Media Platform Providers in Protecting Users through Username Management - Modeong, Riri S; Puluhulawa, Fenty U (Universitas Negeri Gorontalo, 2025)
This article discusses the responsibility of social media platform providers, such as Facebook, in managing and protecting usernames created by users, which are a crucial component of digital identity. With the increasing use of social media globally, misuse of usernames, such as identity theft or account impersonation, poses significant risks to users' reputation and privacy. This research highlights the importance of username protection as part of broader personal data protection, emphasizing the need for platforms to implement effective policies to prevent abuse. Regulations such as Indonesia's Personal Data Protection Law (UU PDP) and the General Data Protection Regulation (GDPR) in the European Union are examined to understand how platforms are required to protect user data, including usernames. The study uses a qualitative approach with literature review and policy analysis methods to analyze existing regulations, as well as interviews with data security experts to explore the challenges faced by platform providers in protecting user identities. The findings indicate that while existing policies and technologies are reasonably adequate, there are still many gaps that can be exploited for identity abuse. Therefore, the research proposes several strategies for social media platform providers to strengthen username protection, including enhancing verification systems, introducing advanced security technologies, and improving abuse reporting systems. These findings are expected to contribute to the ongoing conversation about data privacy and security in the digital age, as well as provide recommendations to protect users' digital identities on social media platforms.